Simulation and Modeling of Detailed Load flow Analysis for the 400kVA and 132kVA Iraqi Grid (Journal of Engineering, 2013)
A load flow program is developed using MATLAB and based on the Newton–Raphson method,which shows very fast and efficient rate of convergence as well as computationally the proposed method is very efficient and it requires less computer memory through the use of sparsing method and other methods in programming to accelerate the run speed to be near the real time. The designed program computes the voltage magnitudes and phase angles at each bus of the network under steady–state operating conditions. It also computes the power flow and power losses for all equipment, including transformers and transmission lines taking into consideration the effects of off–nominal, tap and phase shift transformers, generators, shunt capacitors, shunt inductors, line reactors and bus reactors. Thus, overloaded transformers and transmission lines are identified, and remedial measure can be designed and implemented. It also provides the ability of tie lines, area splitting, and contingency analysis.Any generator station(s) or busbar(s) that exceeds the specified operation limits will be automatically checked and flagged and then the program will automatically suggest the best solution to the problem. It also automatically checks whether the system is sub divided into sub areas or not. If yes, it will find the solution for each area separately. A complete report about the results and the state of the system (the violated generators, busbars, and transmission lines, the required modifications to overcome the violations, the names of the areas splitted,…) will be displayed in working window as well as generating a text file containing all details . It is important to mention that this program is used by the national control center of the Ministry of Electricity and its efficiency was tested through applying the data of the two major Iraqi networks (400kV and 132kV), the program shows very accurate results and provides efficient notes about the status of the networks